Building trust across faith lines - Larson, Marion; Shady, Sara (Journal of Interdisciplinary Studies in Education, 2012)
As educators, we seek to prepare students for a healthy and productive life in the contemporary world.  Given the reality of religious diversity in this world, this paper offers two suggestions. First, the classroom should be utilized as a space where students can better understand their own views on spirituality as well as build bridges that enable meaningful interaction with others who hold views on spirituality that are different from their own.  Second, in order to facilitate encounters with diverse beliefs, trust must be cultivated in the classroom, making it possible for students to learn about and interact hospitably with religious others.